Entomology : novel approaches - Jain, P. C.; Bhargava, M. C. (New India Publishing Agency, 2020)
"The book gives a vast knowledge about the progress made in Indian on different entomological aspects. the book will serve as a complete source book on research techniques and practices of pests management, advanced genetic and biotechnological researches, new pests management technologies on different crops, pesticidal contamination status in environment. The book has been written for teachers, students, researchers and extension workers engaged in pests management strategies."--